Clinical researchThe significance of Y chromosome microdeletion analysis in subfertile men with clinical variocele - Sagnak, Levent; Ersoy, Hamit; Ozok, Ugur; Eraslan, Asir; Yararbas, Kanay; Goktug, Goksel; Tukun, Ajlan (Archives of Medical Science, 2010)
Introduction: The aim of study is determining the cost-effectiveness of detection analysis in the presence of exceptional patients who have mild semen disorders, and beware of unnecessary varicocele repairs; and to ascertain whether patients with clinical varicocele should undergo Y chromosome (Yq) microdeletion analysis as a routine procedure. Material and methods: Varicocele with reflux was diagnosed in 51 male patients with subfertility symptoms upon physical examination (PE), confirmed by scrotal colour-Doppler ultrasound (CDU). After cytogenetic examination, Yq microdeletion analysis was performed on the peripheral blood samples using Promega Y Chromosome Deletion Detection System Version 2. Varicocele repair was performed under general anaesthesia with optical magnification (3-fold) through a subinguinal approach. Results: The mean age of the patients was 27.9. Values of semen concentration ranged from 0 to 72 million/ml, motility from 0 to 65% (A + B) and Kruger from 0% to 18%. The PE revealed normal size and consistency in the bilateral testicles. All patients were cytogenetically normal. However, Yq microdeletion was detected in 2 patients, 1 with mild oligoteratozoospermia and partial AZFb deletion (sY121) and the second patient with severe oligozoospermia and partial AZFc deletion (sY254 and sY255), and they were not subjected to varicocelectomy. Conclusions: The routine performance of pre-operative Yq microdeletion analysis in patients with clinical varicocele does not seem to be cost-effective but the omission of patients with mild oligozoospermia would have subjected them to an unnecessary varicocelectomy and/or further ICSI applications and also would have caused the failure of referral for genetic counselling.